How Can We Interpret the 21st-Century (No Longer) Dramatic Texts and Theatre in Art and Theory? - Tomaž Toporišič (Amfiteater)
The essay analyses the corpora of the dramatic or non-dramatic texts of contemporary authors (Simona Semenič, Milena Marković, Tim Crouch, Oliver Frljić, Katarina Morano and Žiga Divjak, Anja Hilling, Wajdi Mouawad, Dino Pešut and She She Pop) as a border area belonging to both the field of literature and theatre. While detecting the specifics of the interpretation of drama and theatre, the author uses eclectic tools offered by literary and performing arts studies to analyse the corpora of contemporary drama or no longer drama and performing practices. Focusing on a series of contemporary playwrights and theatre directors, he seeks answers to the question of how we can interpret the changes in drama and theatre. How did the specific return to the theatre of words, as defined by the French theorist of contemporary drama Élisabeth Angel-Perez, take place, and to which extent are today’s theatre and drama still post-dramatic but nevertheless establish a new return to the dramatic and dramatised? How do these “experiments belonging to the so-called ‘post-dramatic theatre’ which is also a (post-)deconstructionist theatre, eventually, end up redramatising whatever it was they strove to un/de-dramatize” (Angel-Perez)? Thus, paradoxically, “‘no-longer-dramatic’ texts put forward a new dramaturgical form that subverts the dramatic representation of the world as a fictive whole and accommodates the ‘unsurveyable present’ (Lehmann) of the mediatised-globalised world”.